Progressing delineations of key biodiversity areas for seabirds, and their application to management of coastal seas. (2nd November 2022) - Handley, Jonathan M.; Harte, Emma; Stanworth, Andrew; Poncet, Sally; Catry, Paulo; Cleminson, Sacha; Crofts, Sarah; Dias, Maria
Abstract: Aim: Decision‐making products that support effective marine spatial planning are essential for guiding efforts that enable conservation of biodiversity facing increasing pressures. Key Biodiversity Areas (KBAs) are a product recently agreed upon by an international network of organizations for identifying globally important areas. Utilizing the KBA framework, and by developing a conservative protocol to identify sites, we identify globally importants places for breeding seabirds throughout the coastal seas of a national territory. We inform marine spatial planning by evaluating potential activities that may impact species and how a proposed network of Marine Management Areas (MMAs) overlap with important sites. Location: Southwest Atlantic Ocean. Methods: We collated a national inventory of all breeding locations for seabirds, including abundance records where available, and complementary estimates of at‐sea distribution. We delineated areas of importance in coastal seas following approaches tailored to the ecology of species and assessed areas against global KBA criteria. To determine opportunities for species conservation and management, we reviewed which human activities have been documented to impact the target species globally via IUCN Red List accounts, and also assessed the overlap of important sites with a proposed MMA network. Results: We identified global KBAs for nine seabird species (Anatidae, Diomedeidae, Laridae, Procellariidae, Spheniscidae, Stercorariidae) throughout national coastal seas. Globally important areas where multiple species overlapped were only partially accounted for in key zones of the proposed MMA network. Main Conclusions: Development of a conservative protocol to identify marine sites for assessment against KBA criteria, revealed opportunities for enhancing a network of proposed Marine Management Areas in coastal seas. The framework we apply in this study has broad relevance for other systems where the design or review of management plans for the marine environment is required.